Post-feminism in Cosmopolitan and For Him magazine (FHM) : a critical analysis - Legge, Janet Helen (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics)
Cosmopolitan and For Him Magazine (FHM) are, at present, both the most widely read and, therefore, the most popular "white" consumer magazines in South Africa. They both appeal to young audiences of between 18 and 34 years of age, approximately, and target middle-class, educated groups of readers. My interest in Cosmopolitan and FHM lies in their ability to influence and shape their readers' actions, values, identities and relationships, in particular with the other gender. My analysis is focused on the cover pages and the Editor's letters of six copies of each magazine, ranging from April to September 2003, providing me with a corpus of 12 cover pages and 12 Editor's letters. I adopt a critical perspective through the use of Fairclough's (1989) Critical Discourse Analysis, supported by Mills (1995) Feminist Stylistics, McLoughlin's (2000) textual analysis of cover pages and Kress & van Leeuwen's (1996) visual analysis tools. By combining these different methodologies my research falls into what is newly termed Feminist Critical Discourse Analysis (Lazar 2005). The cover page analyses used primarily McLoughlin and Kress & van Leeuwen and provides an element of pure genre analysis, while the analysis of the Editor's letters were subject to Fairclough's three inter-related stages of analysis, namely: a Description of the formal textual elements of the letters, an Interpretation which analyses the processes of text production and interpretation, and lastly an Explanation of the socio-historical context. Through an analysis of these magazines, whose interests are being served and how the readers are shaped and positioned by the magazines can be identified. My analyses revealed conflicting discourses within each magazine, however it was Cosmopolitan that revealed more tension and conflict in terms of identifying and representing women, while FHM subscribed, for the most part, uniformly to the "new lad" ideology. However, while Cosmopolitan attempted to show a forward-thinking and emancipatory view of the roles of men and women in society, both magazines covertly sustain patriarchal dominance and hegemonic masculinity. In conclusion, I reveal the need for consumers of the mass media to become more critically aware of the ideologies that are promoted through the differing tools of the media and that only through this critical awareness can any further movement towards equal relations between men and women be made.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: For Him Magazine (South Africa); Cosmopolitan (South Africa); Discourse analysis -- Social aspects; Mass media and language; Mass media criticism; Women in mass media; Sex role in mass media; Women in popular culture; Men in popular culture